Financial market volatility and inflation uncertainty: An empirical investigation - Jörg Döpke; Christian Pierdzioch (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1999)
Using monthly data for Germany from 1968 through 1998, the relationship betweenfluctuations of prices in financial markets and inflation is analyzed. The results of Granger-causality tests reveal that stock market has no predictive power volatility for inflation uncertainty, et vice versa. Regarding the subsequent volatility of short-term and of long-term interest rate. In contrast, inflation uncertainty provides some information. The hypothesis of a causality running from the volatility of the real exchange rate to inflation uncertainty cannot be rejected.
Keywords: E31; C32; 330; Inflation uncertainty; financial market volatility; GARCH models; Grangers-causality; Inflation; Risiko; Finanzmarkt; Volatilität; Schätzung; Deutschland